Is testosterone important in LUT function in men and women? ICI‐RS 2015. Issue 4 (April 2017) - Badawi, Jasmin Katrin; Bosch, Ruud; Djurhuus, Jens Christian; Hanna‐Mitchell, Ann T.
Abstract : Aim: This review article is a collaborative report based upon the Authors' presentations and Group discussion on the role of testosterone (T) in the male and female lower urinary tract (LUT) which took place at the 6th International Consultation on Incontinence Research Society's (ICI‐RS) annual meeting, in Bristol, UK (September 8–10, 2015). Methods: It comprises overviews and opinions on both the current state of knowledge of the role of T in LUT function and dysfunction in both sexes. Results: Results from animal studies suggest that T treatment may be beneficial for disorders of the LUT in women including urinary incontinence and pelvic organ prolapse. The need for clinical studies to evaluate the effect of T treatment in peri‐ and post‐menopausal women, taking into account the type of applied androgen, the application form, timing and dosage, is especially emphasized. In males, findings on the impact of T on the male external urethral sphincter underscores that there is still much to learn about its role in male LUT physiology. The important topic of the use of T therapy in the treatment of enuresis in the young, both sexes, is also discussed. The importance of understanding the steroidogenic pathways linking T with estradiol is discussed as being of paramount importance in researching the unique actions of T in the LUT. Conclusion: The overall conclusion is that further research into the role of T in LUT function and dysfunction across genders and age groups (young to old) is extremely important. Neurourol. Urodynam. 36:859–862, 2017 . © 2017 Wiley Periodicals, Inc.